2017
DOI: 10.1371/journal.pone.0183596
|View full text |Cite
|
Sign up to set email alerts
|

Role of amygdala kisspeptin in pubertal timing in female rats

Abstract: To investigate the mechanism by which maternal obesity disrupts reproductive function in offspring, we examined Kiss1 expression in the hypothalamic arcuate (ARC) and anteroventral periventricular (AVPV) nuclei, and posterodorsal medial amygdala (MePD) of pre-pubertal and young adult offspring. Sprague-Dawley rats were fed either a standard or energy-dense diet for six weeks prior to mating and throughout pregnancy and lactation. Male and female offspring were weaned onto normal diet on postnatal day (pnd) 21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
(94 reference statements)
1
32
0
Order By: Relevance
“…Whether these alterations in LH secretion are also influenced by the massive increase in Kiss1 mRNA expression in extra‐hypothalamic sites, such as the amygdala, BNST and lateral septum that we have previously reported in GABAB1KO mice, and which are also regulated by Esr1 similar to Kiss1 neurones in the AVPV/PeN remains to be determined. Interestingly, Pineda et al have very recently demonstrated that amygdala kisspeptin neurones innervate GnRH neurones in the preoptic area and Adekunbi et al have shown that antagonism of medial amygdala kisspeptin delayed puberty onset, disrupted oestrous cyclicity and reduced the incidence of LH surges, giving support to this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…Whether these alterations in LH secretion are also influenced by the massive increase in Kiss1 mRNA expression in extra‐hypothalamic sites, such as the amygdala, BNST and lateral septum that we have previously reported in GABAB1KO mice, and which are also regulated by Esr1 similar to Kiss1 neurones in the AVPV/PeN remains to be determined. Interestingly, Pineda et al have very recently demonstrated that amygdala kisspeptin neurones innervate GnRH neurones in the preoptic area and Adekunbi et al have shown that antagonism of medial amygdala kisspeptin delayed puberty onset, disrupted oestrous cyclicity and reduced the incidence of LH surges, giving support to this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…Evidence that Kiss1 neurones within the MePD have a stimulatory role modulating the GnRH pulse generator is an important development in reproductive neuroendocrinology because it provides further mechanistic insight into why KISS1R receptor antagonism in the MePD was shown to delay puberty, disrupt oestrous cyclicity and reduce the occurrence of the preovulatory LH surge in the rat . The medial amygdala (MeA) is highly‐active in response to a range of external stressors such as restraint, footshock and predatory odour, as well as being involved in the activation of the hypothalamic‐pituitary‐adrenal axis in response to external anxiogenic stimuli; increased levels of adrenocorticotrophic hormne and glucocorticoids are accompanied with stimulation of the MeA .…”
Section: Discussionmentioning
confidence: 99%
“…Control (no optic stimulation) and reduce the occurrence of the preovulatory LH surge in the rat. 10 The medial amygdala (MeA) is highly-active in response to a range of external stressors such as restraint, 35 footshock 36 and predatory odour, 37 as well as being involved in the activation of the hypothalamic-pituitary-adrenal axis in response to external anxiogenic stimuli;…”
Section: Control Period Stimulation Periodmentioning
confidence: 99%
“…Evidence that Kiss1 neurones within the MePD have a stimulatory role modulating the GnRH pulse generator is an important development in reproductive neuroendocrinology, as it provides further mechanistic insight into why KISS1R receptor antagonism in the MePD was shown to delay puberty, disrupt oestrous cyclicity and reduce the occurrence of the preovulatory LH surge in the rat (8). The MeA is highly-active in response to a range of external stressors such as restraint (25), footshock (26), and predatory odour (27), and is involved in the activation of the hypothalamic-pituitary-adrenal (HPA) axis in response to external anxiogenic stimuli; increased levels of ACTH and glucocorticoids are accompanied with stimulation of the MeA (28).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of extra-hypothalamic Kiss1 expression and its receptor in the medial amygdala, and more specifically its posterodorsal subnucleus (MePD) (7), has opened up new possibilities concerning its role in reproductive function. Indeed, we have shown that the MePD Kiss1 neurones are a key upstream regulator of pubertal timing (8), sexual motivation and social behaviour (9). Moreover, we have discovered through neuropharmacological studies that Kp signalling in the MePD per se robustly regulates hypothalamic GnRH pulse generator frequency (10), however, the underlying neural mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%